background image

5.39. EQUIVALENT FILTERS AND REBASE OF FILTERS

129

Definition

713

.

I will call equivalence classes as

unfixed filters

.

Remark

714

.

The word “unfixed” is meant to negate “fixed” (having a par-

ticular base) filters.

Proposition

715

.

A ∼ B

iff

S

A

=

S

B

for every filters

A

,

B

on sets.

3

Proof.

Let

A ∼ B

. Then there is a set

P

such that

P

∈ A

,

P

∈ B

and

A ∩

P

P

=

B ∩

P

P

. So

S

A

= (

A ∩

P

P

)

n

K

Z

K

w

P

o

. Similarly

S

B

= (

B ∩

P

P

)

n

K

Z

K

w

P

o

. Combining, we have

S

A

=

S

B

.

Let now

S

A

=

S

B

. Take

K

S

A

=

S

B

. Then

A ÷

K

=

B ÷

K

and thus

(proposition

711

)

A ∼ A ÷

K

=

B ÷

K

∼ B

, so having

A ∼ B

.

Proposition

716

.

A ∼ B ⇒ A ÷

B

=

B ÷

B

for every filters

A

and

B

and

set

B

.

Proof.

A ÷

B

=

h

B

ui

S

A

=

h

B

ui

S

B

=

B ÷

B

.

5.39.3. Poset of unfixed filters.

Lemma

717

.

Let filters

X

and

Y

be such that Base(

X

) = Base(

Y

) =

B

. Then

X ÷

C

v Y ÷

C

⇔ X v Y

for every set

C

B

.

Proof.

X ÷

C

v Y ÷

C

⇔ X ÷

C

⊇ Y ÷

C

⇔ X ∪

n

K

P

C

K

w

B

o

⊇ Y ∪

n

K

P

C

K

w

B

o

X ⊇ Y ⇔ X v Y

.

Proposition

718

.

X v Y ⇒ X ÷

B

v Y ÷

B

for every filters

X

,

Y

with the

same base and set

B

.

Proof.

X v Y ⇔ X ⊇ Y ⇒ X ÷

B

⊇ Y ÷

B

⇔ X ÷

B

v Y ÷

B

.

Define order of unfixed filters using already defined order of filters of a fixed

base:

Definition

719

.

X v Y ⇔ ∃

x

∈ X

, y

∈ Y

: (Base(

x

) = Base(

y

)

x

v

y

) for

unfixed filters

X

,

Y

.

Lemma

720

.

X v Y ⇔

S

X v

S

Y

for every unfixed filters

X

,

Y

.

Proof.

. Suppose

X v Y

. Then there exist

x

∈ X

,

y

∈ Y

such that Base(

x

) = Base(

y

)

and

x

v

y

. Then

S

X

=

S

x

v

S

y

=

S

Y

.

. Suppose

S

X v

S

Y

. Then there are

x

∈ X

,

y

∈ Y

such that

S

x

v

S

y

.

Consequently

S

x

0

v

S

y

0

for

x

0

=

x

÷

(Base(

x

)

t

Base(

y

)),

y

0

=

y

÷

(Base(

x

)

t

Base(

y

)). So we have

x

0

∈ X

,

y

0

∈ Y

, Base(

x

0

) = Base(

y

0

) and

x

0

v

y

0

, thus

X v Y

.

Theorem

721

.

v

on the set of unfixed filters is a poset.

Proof.

Reflexivity. From the previous theorem.

Transitivity. From the previous theorem.

3

Use this proposition to shorten proofs of other theorem about equivalence of filters? (Our

proof uses transitivity of equivalence of filters. So we can’t use it to prove that it is an equivalence
relation, to avoid circular proof.)